Lady in Cement - Gordon, Douglas; Kazan, Lainie; Martin Gabel; Pat Henry; Raquel Welch; Richard Conte; Steven Peck; Frank Sinatra (USA Arcola Pictures, 1968)
Tony Rome is a miami based detective who while diving in the ocean finds the body of a young woman. He is hired by Gronsky to find her killer. Tony has to sift through a stack of suspects, plus trying to elude the police.
Tony Rome is a miami based detective who while diving in the ocean finds the body of a young woman. He is hired by Gronsky to find her killer...
Marvin H. Albert
Languages : English, Turkish, German, French, Spanish, Italian Subtitles : English, Turkish, German, French, Spanish, Italian, Russian, Czech, Dutch, Serbo-Croatian, Portuguese, Danish, Finnish, Greek, Hindi, Hungarian, Icelandic, Norwegian, Polish, Romanian, Swedish, Arabic, Bulgarian, Hebrew
Keywords: Crime; Drama; Mystery; Thriller; Comedy